Performance of Broiler Chicken as Affected by Replacement of Maize with Pearl Millet and Broken Rice Mixture in the Diet - Bala, Suman; Sharma, R. K.; Khan, Nazam; Rastogi, Ankur; Haq, Zulfqarul (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted on three hundred and twenty, one day old commercial broiler chicks (Cobb strain) to study the effect of replacement of maize by graded levels of pearl millet and broken rice mixture (PBM) on their performance. The birds were randomly divided into four groups (80 birds/group). The experimental diets were: 0% maize replacement (T1), 25% maize replacement with PBM (T2), 50% maize replacement with PBM (T3), 75% maize replacement with PBM mixture (T4). The diets formulated were isocaloric and isonitrogenous as per ICAR (2013). Experiment was conducted for 42 days. The body weight gain (g) was significantly (P<0.05) higher in group T3 (2049.10) in comparison to T1 (1972.00) but the values were statistically similar for T2 (2012.50) and T4 (2009.40) groups. The feed intake was similar irrespective of different dietary treatments. The feed conversion ratio (FCR) was higher in group T1 (1.87) in comparison to T3 (1.78) and T4 (1.80). However, the metabolizability of nutrients, carcass characteristics and blood biochemicalÂ parameters were similar in all the groups except liver weight which was found to be higher (P<0.05) in group T1 in comparison to T3 and T4 with intermediate values for group T2. The feed cost per kg body weight gain in T4 (` 31.64) was significantly (P<0.05) lower than T2 (` 32.69) and T3 (` 32.64) where as for T1, it (` 32.28) was similar to groups T2, T3 and T4. It was concluded that maize may be replaced by PBM in the diet of broiler birds up to 75% without any adverse effect.